IMPLIKASI TERBITNYA REGULASI TENTANG PERTIMAHAN TERHADAP HUBUNGAN ANTARA BOS DAN ANAK BUAH (SEBUAH EGALITARINAISME LOKAL) - Citra Asmara Indra, , S.Sos., M.A (SOSIOLOGI, 2013)
Regulatory  changes  on  tin  by  the  central  government  or  the  entrance  slit  for  local governments  to  take  over  the  management  of  tin  strengthened  by  the  release  of  law  on regional  autonomy.  Government  then  uses  its  authority  to  issue  a  local  regulation  that allows the general public to mine tin unconventional. Unconventional means parties other than  the  two  mining  companies,  namely  PT.  Timah  Tbk.  and  PT.  Koba  Tin  has monopolized the management of lead since the Dutch colonial era, and those who become partners of both companies. Law is a legal umbrella for the people from different walks to mine tin  massively without  any consequences to reclaim their  land dug.  The implications of  rising  regulation  of  the  dynamics  of  tin  tin  mining  in  Bangka  Belitung  province, particularly  in  Lampur  village,  Central  Bangka  regency,  then  look  at  the  pattern  of  the relationship  between  the  boss  and  the  tin  men  in  connection  with  the  issuance  of  these regulations on the lives of the miners.Keyword: Regulation, Minners, and Egalitarism